A study on the factors that contribute to the urban flooding: a case study among staff at Jabatan Pengairan dan Saliran Negeri Melaka / Nurnazimah Yusof and Siti Zulaika Che Mohd Adnan - Yusof, Nurnazimah; Mohd Adnan, Siti Zulaika Che (Faculty of Administrative Science and Policy Studies, 2012)
Malaysia is fortunate in that historically it has not experienced natural disasters in the form of earthquakes, volcanoes, and typhoons. The most common natural disaster frequently encountered in Malaysia is flooding. Flood impact is one of the most significant disasters in the world. More than half of global flood damages occur in Asia. Floods result in losses of life and damage properties. The rise in urban flood damages is simply the increasing number of people and assets that are physically exposed to floods in cities. The fast and unplanned growth of cities results in a larger number of people living in areas potentially liable to flooding. Therefore, a case study among staff at Jabatan Pengairan Dan Saliran Negeri Melaka was conducted in order to investigate factors that contribute to urban flood and how these factors cause to urban flood. By identifying the factors that contributes to urban flooding in Melaka, appropriate actions can be taken to prevent the flood. This study will also provide some suggestions for areas that need improvement. Some strategies can be outlined in order to prevent urban flooding. This department is responsible in flooding matters and physical planning in urban area. About 100 staffs of Jabatan Pengairan Dan Saliran Negeri Melaka participated in the study. Four factors were identified in order to find the most significant factors that contribute to urban flood in Melaka. The factors were rainfall factor, climate change, urbanisation factor and drainage system factor. The Findings showed that a majority of respondents highly agreed that rainfall factor is the most contributor factor to urban flood. It is recommended that in order to have a long-lasting solution to the flooding problems, the city and others in similar situation should embrace sustainable urban drainage systems. Regression analysis showed the most the most significant factors that contribute to urban flood from the four factors that have been identified.